PENGEMBANGAN MODUL MULTIMEDIA MOBILE LEARNING DENGAN ANDROID STUDIO 4.1 MATERI KEANEKARAGAMAN HAYATI BAGI SISWA SMA KELAS X - Ade Suryanda; Ernawati Ernawati; Akbar Maulana (Biosfer: Jurnal Pendidikan Biologi, 2016)
The future competence of the 21st century requires students to be able to utilize Information and Communication Technology (ICT). One of ICTs used by students is smartphone. To get the smartphone benefits used by students, a medium of learning is needed in the form of modules on smartphone operating system. Hopefully, it can make the students feel more interested and motivated in learning biology. The purpose of this study was to develop multimedia mobile learning modules based on android operating system which contains biodiversity material for senior high school students of class X. The research was conducted in September 2015 to January 2016. The research method used was a research and development. The validation test results of subject expert, a linguists and media experts testing obtained scores of 84%, 80.57% and 63%. The trial test results of initial and primary use of students was 81,41% and 81,15%. Next result was a trial test from biology teachers with 87.50%. Pre test obtained an average score 83.98 while the post test gained an average score of 87.23. The conclusion of this research and development was the multimedia mobile learning modules of biodiversity material based on android operating system for senior high school students of class X has been developed, got a good interpretation score and increase student learning outcomes.